Anti-Obesity Drug Delivery Systems: Recent Progress and Challenges - Mohamed M. Ashour; Mostafa Mabrouk; Mohamed A. Aboelnasr; Hanan H. Beherei; Khairy M. Tohamy; Diganta B. Das (MDPI AG, 2023)
Obesity has reached an epidemic proportion in the last thirty years, and it is recognized as a major health issue in modern society now with the possibility of serious social and economic consequences. By the year 2030, nearly 60% of the global population may be obese or overweight, which emphasizes a need for novel obesity treatments. Various traditional approaches, such as pharmacotherapy and bariatric surgery, have been utilized in clinical settings to treat obesity. However, these methods frequently show the possibility of side effects while remaining ineffective. There is, therefore, an urgent need for alternative obesity treatments with improved efficacy and specificity. Polymeric materials and chemical strategies are employed in emerging drug delivery systems (DDSs) to enhance therapy effectiveness and specificity by stabilizing and controlling the release of active molecules such as natural ingredients. Designing DDSs is currently a top priority research objective with an eye towards creating obesity treatment approaches. In reality, the most recent trends in the literature demonstrate that there are not enough in-depth reviews that emphasize the current knowledge based on the creation and design of DDSs for obesity treatment. It is also observed in the existing literature that a complex interplay of different physical and chemical parameters must be considered carefully to determine the effectiveness of the DDSs, including microneedles, for obesity treatment. Additionally, it is observed that these properties depend on how the DDS is synthesized. Although many studies are at the animal-study stage, the use of more advanced DDS techniques would significantly enhance the development of safe and efficient treatment approaches for obese people in the future. Considering these, this review provides an overview of the current anti-obesity treatment approaches as well as the conventional anti-obesity therapeutics. The article aims to conduct an in-depth discussion on the current trends in obesity treatment approaches. Filling in this knowledge gap will lead to a greater understanding of the safest ways to manage obesity.